The New England soul : preaching and religious culture in colonial New England - Stout, Harry S. (Oxford University Press, 1986)
This first comprehensive analysis of preaching in colonial New England uses a multi-disciplinary approach - including analysis of rhetorical style and concepts of identity and community - to examine more than two thousand sermons spanning five generations of ministers, reconstructing the full import of the colonial sermon as a multi-faceted institution that served both religious and political purposes.